El crecimiento de la producción y su incidencia en la tasa de desempleo: una aplicación de la ley de Okun para el Ecuador, 2006.1-2015.4 - Rodríguez Aranda, Andrea Janeth (2017)
A basic objective of any government is to reduce the unemployment rate, which is why policymakers should know the extent to which an economy should grow if it is desired to maintain or reduce this variable in a country. In this sense, Arthur Okun proposed in 1962 a relationship between growth and unemployment - known in the economic literature as the "Okun Law" - in order to calculate or approximate the optimal growth rate to maintain the economy in full employment. Under this proposal, the research topic "Growth of production and its incidence on the unemployment rate: An application of the Okun law for Ecuador, 2006.1-2015.4" is born. The growth of the Gross Domestic Product and the variations in the unemployment rate, through the application of the Okun law for Ecuador during the period 2006.1-2015.4, for which a vector autoregressive model was applied. The secondary information used was obtained from the database of the Central Bank of Ecuador and the National Institute of Statistics and Censuses. From the present investigation it was concluded that in Ecuador there is an inverse relationship between the growth of production and the variation of unemployment. In addition, short-term relationships were found and an Okun coefficient of 5.40 was obtained, implying that an increase in production growth by 1% decreases unemployment by 5.40 percentage points. Keywords: Economic Growth, Unemployment, Cointegration, Production Gap, Employment